Waveform and system design for colocated MIMO radar - Hua, Guang (2014)
This thesis analyzes and develops waveforms and signal processing techniques that are used to improve the performances of range, velocity, and direction-of-arrival (DOA) estimation for multiple-input-multiple-output (MIMO) radar systems with colocated transmit and receive antennas. The main contributions of this work consist of four parts, which are summarized as follows.